Training teachers to follow a task analysis to engage middle school students with moderate and severe developmental disabilities in grade-appropriate literature. - Browder DM; Trela K; Jimenez B (Focus on Autism & Other Developmental Disabilities)
The purpose of this study was to train teachers to follow a task analysis to teach a story-based literacy lesson using adapted, grade-appropriate middle school literature to students with moderate and severe developmental disabilities. A multiple-probe-across-participants design was used to examine the effects of training teachers to follow a literacy lesson plan task analysis on the number of steps completed by teachers on the literacy lesson plan template and changes made by students in response to teachers' use of the literacy lesson plan. Results indicated a functional relationship between teacher training and the number of lesson plan steps followed, with a corresponding student increase in both overall and independent correct responses. Implications for practice and future research are discussed.